Islam, Demokrasi, dan Humanisme Religius: Komparasi Pemikiran Abdurrahman Wahid dan Fethullah Gülen - Nur Julian Majid; Salman Al Farisi (Polyscopia, 2026)
This article examines the relationship between Islam and democracy in the thought of Abdurrahman Wahid and Fethullah Gülen through a comparative framework. It addresses the question of whether democracy is inherently compatible with Islamic principles or constitutes a secular construct in tension with religious doctrine. Employing a qualitative methodology grounded in contemporary Islamic intellectual studies, the research applies interpretative and comparative analysis to the primary works of both thinkers alongside relevant secondary literature. The findings demonstrate that Abdurrahman Wahid articulates democracy within a framework of religious humanism rooted in tawhid, pluralism, and the protection of human rights, whereas Fethullah Gülen emphasizes love, tolerance, and interreligious dialogue as the spiritual foundations of democratic life. Despite differences in socio-historical context and normative emphasis, both thinkers converge in viewing democracy as an ethical arena for realizing justice and human dignity. The study argues that religious humanism provides a viable conceptual bridge between Islam and democratic governance within contemporary Islamic thought.